PRAKTIK PUBLIC RELATIONS DAN CORPORATE SOCIAL RESPONSIBILITY DALAM PERUBAHAN SOSIAL GLOBAL - Juwita, Rina (Interaksi: Jurnal Ilmu Komunikasi, 2016)
ABSTRAKThis paper tries to analyze the trends and patters working in public relations industry in term of Corporate Social Responsibility (CSR). Recent literatures from the PR scholars state that this field requires a broader approach in term of desaigning and implementing CSR rather than just being a small part of management communication function. However, as Clark proposed (2000), these activities should be integrated into the management function and become an important part of management component of the modern public relations. It is true since there are more positive opportunities in the implementation of social responsibility if it is integrated into the PR program if the approaches being used allows the establishment of a stronger relationship between organisation, stakeholders, and the public itself. Â Kata Kunci: Public Relations, CSR, Social Exchange